John F. Kennedy, America's youngest president - Frisbee, Lucy Post.; Fiorentino, Al. (New York : Aladdin Books, 1986)
A biography focusing on the childhood of the youngest man ever elected President (though not to become President) and the youngest ever to die in office.
Keywords: Kennedy, John F. -- 1917-1963 -- Juvenile literature; Kennedy, John F. -- 1917-1963.; Presidents -- United States -- Biography -- Juvenile literature; Presidents